PENDIRIAN USAHA MIKRO KECIL DAN MENENGAH DESA WISATA MERANTI KM.15 BALIKPAPAN - Kety Lulu Agustin; Nurul Musfirah Khairiyah; Erick Sorongan; Amrina Rosyada (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
Located at Kilometer 15, Karang Joang Village, North Balikpapan (Balut) or precisely in Banyumas Village, the Meranti Forest tourist destination is currently in the development stage. Balikpapan Protected Forest Management Unit (KPHL). The manager said that the Meranti tree forest is one of the tourist destinations, because tourism with Meranti tree views has never existed in Balikpapan City at this time. This community service program is carried out at Meranti Tourism, kilometer 15 North Balikpapan with a program implementation time of 5 months starting from April 2022 to October 2022. Community service programs are carried out at Meranti Tourism, Kilometer 15 North Balikpapan, including: Preparation stage, stage design, implementation stage and monitoring stage. To get good work results and reduce problems that arise after work, a survey is needed about the condition of the planned location for making business stalls. Business businesses in the village can create new income for the village community itself, especially the manager of the Meranti tourism village. To encourage the economic welfare of the local community, a business is built, with a general trade partnership pattern, namely a partnership built between the Meranti tourism village community as a place for producing Kelulut Honey.